Enhancing the Use of WordPress to Optimise Guidance and Counselling Services - Tanjung, Romi Fajar; Yosef, Yosef; Sucipto, Sigit Dwi; Rozzaqyah, Fadhlina; Ferdiansyah, Muhammad Aldy; Irawan, Rizky Al Akbar (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2026)
WordPress is a website-based platform that can be used to manage, store, and distribute various types of content with a simple, appealing, and easily accessible interface, as long as the location has an internet connection. With the convenience offered by WordPress, it is necessary to have skills in using this platform to optimise guidance and counselling services that can be accessed by counselees anywhere. Through this platform, counselees can access various guidance and counselling services as well as educational content that can enhance individual potential. The purpose of this training is to improve counsellors’ competence in utilising WordPress for guidance and counselling services. A total of 19 counsellors participated in the activity. To measure the effectiveness of the training, an instrument titled “Evaluation of Counselors’ Competency Improvement in the Use of WordPress” was used. Data analysis was conducted using Excel, Google Forms, and SPSS. The results of the training showed that counsellors’ competence increased, with a pretest–posttest difference of 47.053 and a significance value of 0.000.